Housing stability and the residential context of the COVID-19 pandemic. (21st July 2021) - Jones, Antwan; Grigsby-Toussaint, Diana S.
ABSTRACT: Housing and the residential context where individuals live will be critical to understanding how the COVID-19 pandemic will affect populations across the socioeconomic spectrum, but particularly for racial and ethnic minority and low-income groups in the US.